Anti-H1N1 virus, cytotoxic and Nrf2 activation activities of chemical constituents from Scutellaria baicalensis. (24th December 2015) - Ji, Shuai; Li, Ru; Wang, Qi; Miao, Wen-juan; Li, Zi-wei; Si, Long-long; Qiao, Xue; Yu, Si-wang; Zhou, De-min; Ye, Min
Abstract: Ethnopharmacological relevance: Huang-Qin, derived from the roots of Scutellaria baicalensis Georgi, is a popular Chinese herbal medicine mainly used to treat influenza and cancer. This study aims to elucidate the anti-influenza, anti-cancer and anti-oxidation effective components of S. baicalensis . Materials and methods: Various column chromatography techniques and semi-preparative HPLC were used to isolate Scutellaria compounds, and their structures were identified by HRESIMS and NMR spectroscopic analysis. The pure compounds were evaluated for anti-influenza activities against A/WSN/33 (H1N1) virus in MDCK cells, cytotoxic activities against HepG2, SW480 and MCF7 human cancer cells by MTS assay, and antioxidant activities by Nrf2 luciferase reporter assay. In addition, the contents of 12 major compounds in 27 batches of S. baicalensis were simultaneously determined by a fully validated UPLC/UV method. Results: A total of thirty compounds (1 –30 ), including four new ones (3, 7, 11 and23 ), were isolated from S. baicalensis . Baicalin (15 ), baicalein (26 ), wogonin (27 ), chrysin (28 ) and oroxylin A (30 ) showed potent anti-H1N1 activities, with IC50 values of 7.4, 7.5, 2.1, 7.7 and 12.8 μM, respectively, which were remarkably more potent than the positive drug Osv-P (oseltamivir phosphate, IC50 45.6 μM). Most free flavones (26 –28 and30 ) showed significant cytotoxic activities at 10 μM (up to 61.2% inhibition rate). Furthermore, 30 could activate Nrf2 transcription by 3.8-fold of the control at 10 μM. UPLC analysis indicated the 12 major compounds (including the bioactive ones) accounted for 195.93±43.9 mg g − 1 of the herbal materials. Conclusion: This study demonstrated that free flavones showed potent anti-influenza, anti-cancer and anti-oxidative activities. They are important effective components of S. baicalensis, and can be used as chemical markers for quality control of this herbal medicine. Graphical abstract: